Predictors of health care practitioners' normative attitudes and practices towards sexual and reproductive health and rights: a cross-sectional study of participants from low-income countries enrolled in a capacity-building program. Issue 1 (31st December 2020) - Tumwine, Gilbert; Agardh, Anette; Gummesson, Christina; Okong, Pius; Östergren, Per-Olof
ABSTRACT: Background : Sexual and Reproductive Health and Rights (SRHR) is a concept of human rights applied to sexuality and reproduction. Suboptimal access to SRHR services in many low-income countries results in poor health outcomes. Sustainable development goals (3.7 and 5.6) give a new impetus to the aspiration of universal access to high-quality SRHR services. Indispensable stakeholders in this process are healthcare practitioners who, through their actions or inactions, determine a population's health choices. Often times, healthcare practitioners' SRHR decisions are rooted in religious and cultural influences. We seek to understand whether religious and cultural influences differ significantly according to individuals' characteristics and work environment. Objective : The purpose of this study was to examine the role of healthcare practitioners' individual characteristics and their work environment in predicting normative SRHR attitudes and behaviours (practices). We hypothesized that religion and culture could be significant predictors of SRHR attitudes and practices. Methods : A quantitative cross-sectional study of 115 participants from ten low-income countries attending a capacity-building programme at Lund University Sweden was conducted. Linear regression models were used to assess for the predictive values of different individual characteristics and workplace environment factors for normative SRHR attitudes and SRHR practices. Results : Self-rated SRHR knowledge was the strongest predictor for both normative SRHR attitudes and normative SRHR practices. However, when adjusted for other individual characteristics, self-rated knowledge lost its significant association with SRHR practices, instead normative SRHR attitudes and active knowledge-seeking behaviour independently predicted normative SRHR practices. Contrary to our hypothesis, importance of religion or culture in an individual's life was not correlated with the measured SRHR attitudes and practices. Conclusion : Healthcare practitioners' cultural and religious beliefs, which are often depicted as barriers for implementing full coverage of SRHR services, seem to be modified by active knowledge-seeking behaviour and accumulated working experience with SRHR over time.